Discerning beginning teachers’ conceptions of competence through a phenomenographic investigation - Goh, Pauline Swee Choo; Wong, Kung-Teck (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
The research reported here investigates variation in beginning teachers‟ early experiences of their own teaching competency. A phenomenographic research approach was used to show the qualitatively different ways teacher competence was understood amongst beginning teachers in Malaysia. Phenomenographic interviews were conducted with 18 beginning teachers who had started full time teaching for between 1-3 years. Analysis revealed that beginning teachers „saw‟, „understood‟ the conceptions of competency in five different ways: i) the ability to manage classroom and student behavior, ii) a strong knowledge of the subject content, iii) the ability to reach out for assistance and support, iv) understanding the students they teach, and v) possessing values of professionalism. The relationships between these different ways are represented diagrammatically. This investigation gives an insider‟s perspective a strong voice of what constitutes teacher competence, as well as illustrates that if teacher competence is to be used for any articulation of teacher standards, the term must be carefully defined through the help of the group most affected by any judgements of their competency to avoid misunderstandings, unhappiness and discontentment.